SCHEDULING OPTIMIZATION OF KRI ASSIGNMENTS WITH BINARY INTEGER PROGRAMMING TO SECURE THE KOARMATIM SEA AREA - M Agus Arif H; Budi Santoso W; Ahmadi Ahmadi; Okol S Suharyo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2018)
ABSTRACT Scheduling is an assignment activity related to a number of constraints, a number of events that can occur in a period of time and place or location so that the objective function as closely as possible can be fulfilled. In the hierarchy of decision making, scheduling is the last step before the start of an operation. Scheduling the assignment of KRI in Koarmatim is an interesting topic to be discussed and resolved using a mathematical method. The scheduling process of KRI assignments at Koarmatim is done to produce annual JOP / JOG. This process requires not only rapid follow-up, but also requires systematic steps. The scheduling of assignments applied by Koarmatim is currently carried out by personnel by not using mathematical calculations. The ship assignment scheduling process in this research was carried out using the Binary Integer Programming (BIP) method approach with the aim of minimizing costs and maximizing the purpose of the ship assignment. The scheduling observed was 25 ships carrying out operations for 52 weeks (1 year). The mathematical formulation of the BIP model is made up of one objective function and Three constraint functions. Then the development of the BIP model is then completed, the computer uses Excel Solver. The results obtained that the BIP model applied to scheduling KRI Koarmatim assignments is the maximum coverage area reached is 93,651,234 NM2, with an area safeguard level of 76,11 from the entire area of operating sector I to IX (1,230,442 NM2). BIP is an appropriate method to be used as a method in scheduling the assignment of KRI in Koarmatim. Keywords: Scheduling, Ship assignments, Binary Integer Programming